Cochlear neuropathy in the rat exposed for a long period to moderate‐intensity noises. Issue 6 (3rd February 2015) - Gannouni, Noura; Lenoir, Marc; Ben Rhouma, Khemais; El May, Michèle; Tebourbi, Olfa; Puel, Jean Luc; Mhamdi, Abada
Abstract : Damaging effects on the cochlea of high‐intensity acoustic overexposures have been extensively documented, but only few works have focused on the danger of moderate noise levels. Using scanning and transmission electron microscopy, we explored the noise‐induced neuroepithelial changes that occur in the cochlea of rats subjected to moderate intensities, 70 and 85 dB SPL, for an extended period of time (6 hr/day over 3 months). Although the full quota of outer and inner sensory hair cells remained present, we detected discrete abnormalities, likely resulting from metabolic impairment, in both types of hair cell within the basal region of the cochlea. In contrast, important noise‐dependent losses of spiral ganglion neurons had occurred. In addition, we found cytoplasmic accumulations of lipofuscin‐like aggregates in most of the surviving cochlear neurons. These results strongly suggest that noise levels comparable to those of certain working environments, with sufficient exposure duration, pose a severe risk to the cochlea. Moreover, our data support the notion that long‐duration exposure to moderate noise is a causative factor of presbycusis. © 2015 Wiley Periodicals, Inc.